Why don't we apply vitamin E to skin care? (International Journal of Food and Nutritional Sciences, 2022)
Objectives: Reviewing topical and systemic tocopherols as potential treatments for skin diseases in light of the extensive usage of vitamin E by patientsl.Data sources: Index Medicus was searched for articles published between 1922—1966, the year vitamin E was discovered (the beginning of MEDLINE). We looked for papers on vitamin E or tocopherol in dermatology in both English and French in MEDLINE. From the review papers' reference lists, additional original articles were found.Study choice: Anecdotes and open studies are cited for completeness and as guidance for future study; only well-designed controlled studies were approved.Synthesis of data: There is some flimsy or conflicting evidence that vitamin E helps with collagen synthesis, wound healing, epidermolysis bullosa, cancer prevention, claudication, and yellow nail syndrome. It was useless for treating psoriasis, atopic dermatitis, dermatitis herpetiformis, subcorneal pustular dermatosis, porphyrias, and UV-induced skin damage.Conclusions: There is still no evidence of vitamin E's usefulness in treating specific dermatologic disorders after 44 years of research. To further understand vitamin E's function, more study in carefully planned controlled studies is required.